Incidence Trends of Inflammatory Bowel Disease in a Southern European Country: A Mirror of the Western World?. Issue 5 (28th May 2022) - Santiago, Mafalda; Stocker, Francisco; Ministro, Paula; Gonçalves, Raquel; Carvalho, Diana; Portela, Francisco; Correia, Luís; Lago, Paula; Trindade, Eunice; Dias, Cláudia Camila; Magro, Fernando
Abstract : INTRODUCTION: Inflammatory bowel disease (IBD) affects people from all age categories worldwide. Although the incidence of the disease is stabilizing or decreasing in most Western world countries, its prevalence is still increasing because of the rise in life expectancy and better disease management. This work intends to identify the trends related to IBD incidence nationwide, analyzing regional, sex, and age distributions. METHODS: Data were provided by the Portuguese Shared Services of the Ministry of Health. This study consisted of a retrospective analysis of all first consultations coded for "Chronic enteritis/ulcerative colitis" (D94) in a primary healthcare setting, between 2017 and 2020, in Portugal. The primary outcome measure was the IBD incidence rate per 100, 000 inhabitants. We also calculated the incidence rate per person-year and forecasted incidence until 2024. RESULTS: Between 2017 and 2019, the incidence rate of IBD in Portugal decreased from 54.9 to 48.6 per 100, 000 inhabitants. The average incidence was 20 new cases of IBD per 1, 000 person-year. It was predicted that, in December 2023, IBD incidence would reach 305.4 new cases (95% Prediction Interval 156.6–454.3), a similar result to the values forecasted for December 2021 (305.4, 95% Prediction Interval 197.3–413.6). DISCUSSION: The incidence of IBD slightly declined from 2017 to 2019, and it is posed to stabilize in the future. The presented data are of the utmost importance for the characterization of IBD in Southern European countries and the establishment of future health policies in the setting of compounding prevalence in the Western world.